Effect of curing regime on the immobilization of municipal solid waste incineration fly ash in sustainable cement mortar - Baoju Liu, Baoju Liu; Lei Yang, Lei Yang; Jinyan Shi, Jinyan Shi; Shipeng Zhang, Shipeng Zhang; Çağlar Yalçınkaya, Çağlar Yalçınkaya; Abdullah Faisal Alshalif, Abdullah Faisal Alshalif (Elsevier, 2023)
Stabilizing/solidificating municipal solid waste incineration fly ash (MIFA) with cement is a common strategy, and it is critical to study the high-value utilization of MIFA in ordinary Portland cement (OPC) components. With this aim, binary-binding-system mortar was produced by partially replacing OPC (~50%) with MIFA, and the effects of different curing regimes (steam curing and carbonation curing) on the properties of the cement mortar were studied. The results showed that the setting time of the cement paste was shorten with the increase of MIFA content, and steam curing accelerated the hardening of the mixture. Although the incorporation of MIFA reduced the strength of the mortar, compared to conventional curing method, steam curing and carbonation curing increased the 3-d strength of the mortar. For high-volume MIFA mortars, the CO2-cured samples had the highest long-term strength and lowest permeability. The incorporation of MIFA increased the initial porosity of the mortar, thereby significantly increasing the carbonation degree and crystallinity of the reaction product - CaCO3. Steam curing also further narrowed the difference in the hydration degree between MIFA-modified sample and plain paste, which may be due to the enhanced hydraulic reactivity of MIFA at high temperatures. Although the incorporation of MIFA increased the porosity of the mortar, this waste-derived SCM refined the bulk pore structure and decreased the interconnected porosity. Additionally, the heavy metal leaching contents of MIFAmodified mortars were all below 1%, which meet the requirements of Chinese standards. Compared with standard curing, steam curing and carbonation curing made the early-age and long-term performance of MIFAmodified mortar better, which can promote the efficient application of MIFA in OPC products.